The Role of 5S Workplace Organization in Promoting A Safe Work Environment in the Petroleum Sector: An Exploratory Study of the Opinions of Oil Sector Officials in Najaf Al-Ashraf - Al-Hashimee, Yaser Hameed Mohammad; Nasab, Mahdi Mohammadi (Journal of Economic, Administrative and Legal Sciences, 2025)
Amid the growing challenges of the contemporary business environment, which necessitate keeping pace with competitive changes and enhancing the ability to grow and survive, the importance of improving production processes by adopting effective methodologies such as the 5S methodology becomes evident. This study examines the impact of implementing this methodology on enhancing a safe work environment in the oil sector in Najaf Governorate (Iraq), by addressing the central question: What is the impact of organizing the workplace according to the 5S methodology on achieving a safe work environment?  The study aims to provide a theoretical and practical framework linking the independent variable (applications of the 5S methodology: Sort, Set in Order, Shine, Standardize, Sustain) and the dependent variable (safe work environment with its pillars: occupational safety and health management, environmental management, and human resources management). It focuses on raising awareness among administrative leaders about the importance of an effective organizational structure in addressing deviations during work.   The study adopted a mixed methodology combining theoretical analysis (a review of literature related to the 5S methodology and work environment) and field research (a survey of a purposive sample of 25 administrative and technical leaders in the Najaf oil sector, including managers, engineers, and technicians). The research addressed the following questions: What are the fundamental dimensions of the 5S methodology in organizing workplaces?. Is there a correlational relationship between the dimensions of the methodology and the dimensions of a safe work environment?. To what extent does the application of 5S improve the quality of the safe environment?   Key findings include: The majority of participants supported the feasibility of applying the 5S methodology dimensions in the oil sector. The study’s hypotheses were confirmed, revealing a strong correlational relationship and a clear impact of the methodology in enhancing the safe environment.